2002
DOI: 10.1007/s100670200019
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Syndrome Associated with Lung Interstitial Disorder in a Dental Technician Exposed to Ceramic Silica Dust. A Case Report and Critical Literature Review

Abstract: Exposure to silica minerals is associated with silicosis and autoimmune disorders, especially systemic scleroderma. Evidence of this association has been increasingly reported in the last decade. The aim of this paper is to discuss, on the basis of a literature review, the case of a 28-year-old female dental technician who suffered from episodes of weakness, arthralgia, pain, swelling and stiffness of the fingers, dyspnoea with cough, a positive Waaler-Rose reaction, increased rheumatoid factor and normal ESR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…The immunological features of patients with SIL , who have been exposed to silica but not to asbe stos , have been investigated clinically and experimentally because ofthe frequent complications ofautoimmune diseases (19)(20)(21). We have been focusing on the Fas-mediated apoptotic pathway in lymphocytes (22)(23)(24) and also on various autoantibodies (25)(26)(27) in SIL patients and have reported that Fas-mediated apoptosis is impaired in SIL patients.…”
Section: Tcr-vj3 Analyses Of Silica and Asbestos-related Disordersmentioning
confidence: 99%
“…The immunological features of patients with SIL , who have been exposed to silica but not to asbe stos , have been investigated clinically and experimentally because ofthe frequent complications ofautoimmune diseases (19)(20)(21). We have been focusing on the Fas-mediated apoptotic pathway in lymphocytes (22)(23)(24) and also on various autoantibodies (25)(26)(27) in SIL patients and have reported that Fas-mediated apoptosis is impaired in SIL patients.…”
Section: Tcr-vj3 Analyses Of Silica and Asbestos-related Disordersmentioning
confidence: 99%
“…In this study, to elucidate the role of Treg in silicosis patients, the frequency in peripheral blood and function of Treg were examined, since silicosis may be the pre-clinical status for autoimmune diseases (1)(2)(3)(4). In addition, our previous results indicated that in silicosis patients, who did not manifest clinical signs and symptoms of autoimmune diseases, possessed the dysregulation of Fas-mediated apoptotic pathway in their lymphocytes and was disrupted (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The most common finding in DTP patients is round nodules on HRCT (5). Studies have reported radiologic abnormalities such as diffuse reticulonodular infiltration, calcified lymph nodes, small opacities (International Labour Organization [ILO] category ≥1/0), and diffuse interstitial disorder in DTP; however, this is the first report of conglomerated lymphadenopathy and increased PET uptake (1,2,7,8).…”
Section: Discussionmentioning
confidence: 79%